Estimation of Individual Wave Solutions for the Nonlinear Dynamic Model in A Heterogeneous Quantum Magnetoplasma - Zeynab Kiamehr; Zohreh Kiamehr (Journal of Sciences, Islamic Republic of Iran)
In this paper, a quantum plasma system was considered to study a nonlinear turbulence model. The properties of nonlinear propagation of the solitary potential wave in two-dimensional heterogeneous quantum magnetoplasma were investigated using the quantum hydrodynamic model. It was assumed that in addition to the heterogeneity in this system, there is a magnetic field. If the collision frequency between the heavy particles (ions and neutral particles) is negligible, a nonlinear equation in two dimensions (2D), as well as the solutions of the plasma electrostatic potential, are obtained. For this purpose, the method of indeterminate coefficients, dimensionless conversion, travel wave conversion, etc. were used. A series of corresponding physical quantity properties was described by solving the individual solution of wave obtained for a quantum plasma system with a nonlinear model. The effects of the quantum Bohm potential on the single wave structure of the electrostatic potential are shown numerically in Figures 1 and 2. It was found that increasing the numerical density and amplitude of this wave decreases. The present study may play a significant role in understanding the properties of potential wave propagation in dense astrophysical plasma where quantum effects are useful.